Regional Policy Coherence for the Great Green Wall Initiative: Strengthening Synergies for the Sustainable Management of Africa’s Forests - African, Union (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
Achieving sustainable forest management and climate resilience in Africa’s drylands requires greater alignment between regional strategies that address land degradation, deforestation, and biodiversity loss. This policy brief explores the critical need for coherence between the African Union’s Great Green Wall Initiative Strategy and Ten-Year Implementation Framework (GGWI Strategy) (2024–2034) and the Sustainable Forest Management Framework for Africa (SFMF) (2020–2030). Both frameworks are vital instruments in advancing tree-based restoration, improving rural livelihoods, strengthening food security, and enhancing climate resilience. While the GGWI Strategy and SFMF share strong commitments to ecosystem restoration, community development, and resilience-building, their full potential can only be realised through integrated planning, harmonised implementation, and aligned investment approaches. Differences in ecological scope, sectoral priorities, and financing visibility -including access to carbon finance - must be addressed to unlock synergies. Strategic coherence will improve on-the-ground implementation, enhance resource efficiency, and increase access to both public and private investment. This policy brief calls for the establishment of a joint task force among African Union institutions, Regional Economic Communities, and implementation partners to coordinate efforts, align monitoring systems, and mobilise joint financing. Such alignment will not only accelerate the achievement of continental and global commitments - including Agenda 2063, the United Nations Decade for Ecosystem Restoration, and the newly adopted United Nations Decade for Afforestation and Reforestation (2027–2036) - but also ensure that Africa’s forests become a cornerstone of inclusive, climate-resilient development.